The impact of hate crime trauma on gay and lesbian interpersonal relationships - Sanders-Hahs, Erin M. (Kansas State University, 2008)
Homophobic hate crimes against lesbians and gay men represent a significant social problem that has important psychological consequences for survivors. Because the nature of these crimes is, by definition, against someone for his or her intrapersonal traits, it has even more potential to be damaging to a victim and in turn potentially detrimental to the development and/or maintenance of close personal relationships. The impact of trauma has long been studied from the view of the trauma survivor or any secondary traumatization of those around the primary survivor. The impact of hate crime victimization has also been examined, and it, too, has also been examined from the primary survivors perspective. Only in recent years has the impact of trauma on interpersonal relationships been examined. Additionally, there is currently little to no literature on the impact of trauma or traumatic events on gay or lesbian relationships. The types of hate crime victimization experiences range from verbal abuse to severe physical assault to death. While hate crime victimization is not specifically identified in the DSM – IV – TR as a potentially traumatic event, physical assault, which is found commonly in hate crimes, is identified. Therefore, hate crime victimization could be a potentially traumatic event. However, this has not been addressed in the traumatic stress field. This report is intended to address the gaps in the current body of literature in both the traumatic stress field and the gay and lesbian literature. This overwhelming lack of literature has the potential to be very detrimental to professionals working with this population and in turn detrimental to the population and society. Evidence suggests that there may be a difference in how or if the potentially traumatic hate crime victimization experience manifests itself internally or in other forms because of the nature and severity of the victimization in one or both partners. Evidence also suggests, similarly to heterosexual couples, the impact of trauma has repercussions throughout the couple relationship. This report provides a preliminary start to continue and expand the work with the gay and lesbian community.
Keywords: Gay; Lesbian; Hate crime; Trauma; Couples; Health Sciences, Mental Health (0347); Psychology, General (0621)